ANALISIS KEPUTUSAN PEMBELIAN MELALUI KEPUASAN PELANGGAN DITINJAU DARI KUALITAS PELAYANAN DAN HARGA PADA CAFÉ AOLA - Yuli Tata Alfin Hamidah; Rudi Wibowo; Yulie Wahyuningsih (Fakultas Ekonomi, 2026)
This study was motivated by the rapid growth of the culinary industry, which has intensified competition among cafés. In such a context, service quality and price are often considered key factors that influence consumers’ purchasing decisions. However, prior studies have produced inconsistent findings, creating a research gap that warrants further investigation by incorporating customer satisfaction as a mediating variable. Therefore, this study aims to analyze the effects of service quality and price on purchasing decisions through customer satisfaction at Cafe Aola Lamongan. This research employed a quantitative approach using a survey method. Data were collected through questionnaires administered to 100 respondents who had purchased products at Cafe Aola Lamongan. The sampling technique used was accidental sampling. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. The results showed that service quality had no significant effect on purchasing decisions. Similarly, price also had no significant effect on purchasing decisions. In addition, service quality did not significantly affect customer satisfaction, and price did not significantly affect customer satisfaction. Conversely, customer satisfaction was found to have a positive and significant effect on purchasing decisions. Furthermore, the mediation analysis indicated that customer satisfaction was unable to mediate the effects of service quality on purchasing decisions or the effects of price on purchasing decisions at Cafe Aola Lamongan. In conclusion, purchasing decisions at Cafe Aola are more strongly influenced by customers’ satisfaction than by service quality and price directly. These findings support the Theory of Consumer Behavior, which suggests that consumers make purchasing decisions after evaluating the benefits and experiences they receive. Therefore, Cafe Aola is expected to prioritize strategies that can enhance customer satisfaction to strengthen customers’ purchasing decisions.